Emerging trends in ICT security - Akhgar, Babak; Arabnia, Hamid (Morgan Kaufmann/Elsevier, 2014)
Discusses the foundations and theoretical aspects of ICT security. This title covers trends, analytics, assessments and frameworks necessary for performance analysis and evaluation. It gives you the knowledge needed for successful deployment of security solutions in many environments.